Optical Manipulation with Plasmonic Beam Shaping Antenna Structures. (26th August 2012) - Jun, Young Chul; Brener, Igal
Abstract : Near-field optical trapping of objects using plasmonic antenna structures has recently attracted great attention. However, metal nanostructures also provide a compact platform for general wavefront engineering of intermediate and far-field beams. Here, we analyze optical forces generated by plasmonic beam shaping antenna structures and show that they can be used for general optical manipulation such as guiding of a dielectric particle along a linear or curved trajectory. This removes the need for bulky diffractive optical components and facilitates the integration of optical force manipulation into a highly functional, compact system.